Analysis of The Arabic Textbook for Class IV of Madrasah Ibtidaiyah by Sri Kuryati - Jalaludin, Abdul; Maesyaroh, Atiqotul; Ezriyati, Ezriyati (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the suitability of Sri Kuryati's Arabic textbook based on KD (Basic Competence) KMA (Minister of Religion Decree) 183 2019 and the quality of the Arabic textbook. This type of research uses qualitative research. The results of this study are: 1) Sri Kuryati's Arabic Textbook, in general, has met the specified standards, namely a) In chapter I, the author has presented the subject matter according to the linguistic elements of a simple text related to the theme of Ø§Ù„Ø§ by linking speech acts by giving each other. Information about a person's address and describe the linguistic components related to Ø§Ù„Ø§Ù†, b) In chapter II, the author has presented the main material according to the linguistic elements of a simple text related to the Ø§Ù„ theme and explained the structure of Ø§Ù„Ø¶Ù…ÙŠØ±Ø§Ù„Ù…Ù†ÙØµÙ„â€“Ø§Ù„Ø§Ø´Ø§Ø±Ø© and connected speech acts by outlining expressions, c) In chapter III the author has presented the main material according to linguistic elements through simple texts related to the Ø§Ù„ theme as well as communicative and instructional expressions in the learning process and from the three chapters still need improvement in the presentation of the material, 2) The text of the book, in general, has good quality through four aspects, namely asp oak selection, aspects of gradation, aspects of presentation and aspects of repetition.